1995
DOI: 10.1038/hdy.1995.81
|View full text |Cite
|
Sign up to set email alerts
|

Molecules versus morphology: the detection of selection acting on morphological characters along a cline in Drosophila melanogaster

Abstract: This work examines the nature of north-south clinal variation in morphological characters in Drosophila melanogaster. Isofemale lines were established from flies collected along a transect extending from Winnipeg, Manitoba (Canada) to Tampa Bay, Florida (U.S.A.). Offspring from different lines within each location were then cultured under standardized conditions and used to examine phenotypic variation in seven morphological characters along the dine. In addition, allozyme variation at seven polymorphic loci w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
2
2

Year Published

2001
2001
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 42 publications
2
58
2
2
Order By: Relevance
“…The interaction effect (␣␤ ij ) reflects the lack of proportionality between allozyme (F ST *) and quantitative (Q ST *) differentiation. If the two measures of differentiation are proportional over the set of populations compared, the absence of selection acting on the quantitative trait is assumed and incremental effects are attributed to the different kind of data analysed (Long and Singh, 1995). Great differences in patterns of population subdivision were present for the traits analysed.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The interaction effect (␣␤ ij ) reflects the lack of proportionality between allozyme (F ST *) and quantitative (Q ST *) differentiation. If the two measures of differentiation are proportional over the set of populations compared, the absence of selection acting on the quantitative trait is assumed and incremental effects are attributed to the different kind of data analysed (Long and Singh, 1995). Great differences in patterns of population subdivision were present for the traits analysed.…”
Section: Resultsmentioning
confidence: 99%
“…Long and Singh (1995) showed that the choice of enzyme systems may result in a difference between quantitative and allozyme population subdivision, which is not because of the action of natural selection. To avoid this pitfall they proposed to compare pairs of populations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations